KEBERLANJUTAN ARSITEKTUR TRADISIONAL ACEH PADA PERKEMBANGAN RUMAH TINGGAL: MASSA DAN ARTIKULASI RUMOH ACEH - Sarvina Fitri Rizky (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
The new architecture requires the involvement of traditional architecture in keeping the continuity of the past. It is a must to keep the local identity. Thus, this paper discusses the continuity of Acehnese traditional house architecture, Rumoh Aceh, in the houses which developed in Lambheu Village. Many discussion had discussed its form continuity, but it was a rare discussion related to its other certain parts. Where every parts are what configurate the whole shape of architecture. Thus, this current study highlighted mass and articulation, as part of form configuration, to have deep analyzing on past and current condition of traditional characteristics. The aim of this study was to grow awareness of the continuity of past architecture by drawing an overview of its current condition. The parameters used to study mass and articulation are based on the theory of Baper and Hassan (2012). The research was carried out by observing the mass and articulation of the housing development and then qualitatively analyzed by comparing its conditions to the mass and articulation character of Rumoh Aceh. The results showed that mass and articulation continuity was poorly occurred.